“It's Just Like on TV”: An Analysis of the Mirandizing Process on TV - Wing, Dakota (Criminal justice review, 2025)
When Mirandizing a suspect, officers sometimes compare the Mirandizing process to their representation on TV. In doing so, officers assume the suspect (and more generally the American public) is familiar with, and understands, their Miranda warnings due to their dissemination on TV. Thus, this paper investigates how the Mirandizing process is presented on TV. An analysis of arrests and custodial interviews on Law & Order: SVU indicates that fictional suspects are rarely adequately Mirandized; they are either not Mirandized at all or are provided a partial version. Moreover, suspects on TV are found to attempt to explicitly invoke their rights only 11% of the time, of which there is about a 50–50 chance of the attempted invocation being successful. In 23% of the time, legal representation appears without any language from the suspect showing them invoking their rights. Attempted and implied invocations on TV are primarily made by persons guilty of the crime they are being accused of, and innocent suspects primarily waive their rights, reinforcing a popular belief that guilty people invoke their rights and innocent people waive them.